Reader in Trinitarian Theology - van der Westhuizen, Henco (UJ Press, 2023)
"Speaking God today ... signifies assuming the task constitutive of the discipline of systematic theology. ... A relational God who lives in ex-static self-giving, creates Christian communities of hospitality and generosity, and offers a healing vision of truth, goodness, and beauty. Speaking the Triune God extends the promise of the benediction, May the grace of the Lord Jesus Christ, and the love of God, and the fellowship of the Spirit be with you all." Rian Venter In this first volume on doing Theology in South Africa, Henco van der Westhuizen assembled an array of articles by South African theologians on Trinitarian Theology from 1976 to today.